First episode psychosis patients show impaired cognitive function – a study of a South Asian population in the UK. (April 2013) - Saleem, Majid M; Harte, Michael K; Marshall, Kay M; Scally, Andy; Brewin, Anita; Neill, Jo C
Background: Cognitive deficits are a core symptom of schizophrenia, severely debilitating and untreated by current medication. However, to date there is limited research focusing on the precise nature of the cognitive disturbances at first episode in ethnic populations. Improved understanding of this will allow improved approaches to therapy. The aim of this study was to investigate cognitive function with a first episode of psychosis South Asian patients. Methods: Twenty South Asian first episode psychosis patients and 15 healthy South Asian matched controls were recruited. All were second generation South Asian people living in the UK. Subjects who took part in the study completed the Positive and Negative Syndrome Scale (patient group), the Wechsler Test of Adult Reading and a battery of neuropsychological assessments to assess specific domains of cognition of relevance to Measurement and Treatment Research to Improve Cognition in Schizophrenia using the Cambridge Neuropsychological Test Automated Battery (CANTAB) (all groups). Results: Results show that first episode patients performed significantly worse than controls across all cognitive domains tested using CANTAB. Significant impairments were found in tests of visual and spatial memory, executive function, working memory, spatial planning and attention. Importantly, a number of cognitive performance indices (visual memory, spatial memory, executive function) were positively correlated with the severity of negative symptoms. Conclusion: We demonstrate that first episode South Asian patients display significant and specific cognitive deficits with evidence to support an association between negative symptoms and certain cognitive domains at first episode in this patient population.